First of all, write these in a way people can read them in the future. Don't make it so hard to help you.
Secondly:
Given that a♥b = 2a(32− b)
If a♥b = −23, solve for b in terms of a.
A) b = 16a + 32
B) b = 13a + 32
C) b = 12a + 32
D) b = 16a − 32
-23 = 2a(32− b), devide both sides by 2a -23/2a = 32 - b, subtract 32 from both sides -23/2a - 32 = -b, multiply both sides by -1 23/2a + 32 = b
verified:
b = 23/2a + 32
-23 = 2a(32 − (23/2a + 32))
-23 = 2a(32 -23/2a -32)
-23 = 2a(-23/2a)
-23 = -23
Are you sure you copied this correctly?